2014
DOI: 10.2139/ssrn.2534977
|View full text |Cite
|
Sign up to set email alerts
|

Better Residential than Ethnic Discrimination! Reconciling Audit's Findings and Interviews' Findings in the Parisian Housing Market

Abstract: Laboratoire interdisciplinaire d'évaluation des politiques publiques LIEPP Working Paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The low access to homeownership of North African immigrants is not surprising, considering that they are on average low-skilled and thus less able to accumulate wealth to purchase a home. They may also suffer from discrimination on the housing market, although it is debated whether discrimination in France is based mostly on taste or the place of residence (Combes et al, 2012;Bonnet et al, 2015).…”
Section: Immigration and Homeownership In Francementioning
confidence: 99%
“…The low access to homeownership of North African immigrants is not surprising, considering that they are on average low-skilled and thus less able to accumulate wealth to purchase a home. They may also suffer from discrimination on the housing market, although it is debated whether discrimination in France is based mostly on taste or the place of residence (Combes et al, 2012;Bonnet et al, 2015).…”
Section: Immigration and Homeownership In Francementioning
confidence: 99%
“…Scheepers et al (2013) found similar results: both ethnic composition and economic poverty indicators determined different dimensions of ‘hunkering down’. Besides, Bonnet et al (2016) found that the invitation rates are lower for citizens living in deprived neighbourhoods, without affecting the level of ethnic discrimination. Therefore, they state that taste-based discrimination can be based on the taste for space or ethnicity.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Others find a positive (Baldini and Federici, 2011) or no relation (Van der Bracht et al, 2014). Besides, Bonnet et al (2016) propose the possibility that discrimination based on tastes for ethnicity may go together with tastes for space. This could lead to residential discrimination next to ethnic discrimination.…”
Section: Introductionmentioning
confidence: 99%